2022
DOI: 10.32412/pjohns.v37i2.2025
|View full text |Cite
|
Sign up to set email alerts
|

A Makeshift Blue Light Filter for Endoscopic Identification of Traumatic Cerebrospinal Fluid Leak Using Fluorescein

Abstract: ABSTRACTObjective: To describe a makeshift blue light filter for endoscopic visualization of a traumatic cerebrospinal fluid leak repair using intrathecal fluorescein and its application in one patient. Methods:Study Design:Surgical Instrumentation Setting:Tertiary Government Training Hospital Patient:One Results: Intra-operative endoscopic identification of fistulae sites was achieved using intrathecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In other words, these methods have limitations as initial diagnostic tools. Magnetic resonance cisternography has the advantage of requiring no intrathecal contrast agent injection, and T2-weighted images with high signal intensity can be helpful for localizing CSF leakage points [ 24 ]. However, the lack of information on bony structures and the high cost (more than five times higher than HRCT) reduce the attractiveness of magnetic resonance cisternography for initial leakage point localization [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, these methods have limitations as initial diagnostic tools. Magnetic resonance cisternography has the advantage of requiring no intrathecal contrast agent injection, and T2-weighted images with high signal intensity can be helpful for localizing CSF leakage points [ 24 ]. However, the lack of information on bony structures and the high cost (more than five times higher than HRCT) reduce the attractiveness of magnetic resonance cisternography for initial leakage point localization [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of information on bony structures and the high cost (more than five times higher than HRCT) reduce the attractiveness of magnetic resonance cisternography for initial leakage point localization [ 6 ]. Recently, in addition to imaging tools, studies have been reported that can effectively check the CSF leak site using an endoscope equipped with a blue light filter after intrathecal fluorescein administration, increasing the number of options for diagnostic testing [ 24 ].…”
Section: Discussionmentioning
confidence: 99%